PENGARUH CITA RASA, HARGA, DAN KUALITAS PRODUK TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA PIVY SWEET DI SITUBONDO - Rico Arif Pratama; Ida Subaida; Siti Soeliha (Fakultas Ekonomi dan Bisnis, 2025)
Marketing plays a crucial role within a company, particularly in external environments, such as market dynamics. This study aims to analyze and test the influence of taste, price, and product quality on customer loyalty, with customer satisfaction as an intervening variable, in the context of the Pivy Sweet business in Situbondo. The population in this study consists of Pivy Sweet’s customers, and the sampling method used is probability sampling. Data analysis and hypothesis testing were conducted using the Structural Equation Modeling–Partial Least Squares (PLS-SEM) approach. The hypothesis testing results, conducted using Smart PLS 3.0, indicate that taste has a significant positive effect on customer satisfaction, and price also has a significant positive effect on customer satisfaction. Meanwhile, product quality has a positive but not significant effect on customer satisfaction. Furthermore, taste has a positive but not significant effect on customer loyalty; price has a significant positive effect on customer loyalty; and product quality has a significant positive effect on customer loyalty. Customer satisfaction also has a significant positive effect on customer loyalty. Additionally, both taste and price have a significant positive impact on customer loyalty, contributing to customer satisfaction. In contrast, product quality has a positive but not statistically significant indirect effect on customer loyalty through customer satisfaction.